The Internet of Things and Artificial Intelligence-Based Recommendation System for Automating Homes - Sudhamsu, Gadug; Kumar, Ravi; Desai, Karishma; Yadav, Dhananjay Kumar; Pandey, Pratik (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Automation techniques for the home are becoming more popular as a result of the simplicity with which equipment and appliances may be controlled by speech or centered on physical activity by the use of sensors. Research suggests that introducing smartness to small businesses and regular users may be expensive and that there has to be an easier, more transparent, and more simple way to connect and manage equipment with mobile apps. Sensors and the Internet of Things (IoT) have enabled the rapid development of several electrical appliance prototypes into marketable final products. In this information time, there are not enough data-driven strategies for making the most of ceiling fans in homes and businesses. As a further advantage, Artificial Intelligence (AI) algorithms applied to data may help us uncover patterns that reflect appliance use and spot shifts in our daily routine. As a result, this study suggests a method to promote specific programs to those who have smart homes via the usage of IoT and AI. With the resident’s permission, the dataset includes information on the fans in their bedroom, living room, and lounge. A wide variety of experts, including data scientists, environmentalists, fan makers, architects, and social scientists, may benefit from this information. Monthly averages of temperature and humidity, energy used, hours of use per day or month, and monthly/weekly summaries are all available for analysis.